2021
DOI: 10.1039/d0fo02834g
|View full text |Cite
|
Sign up to set email alerts
|

A recent update on the multifaceted health benefits associated with ginger and its bioactive components

Abstract: The bioactive compounds and bioactivities of ginger, and their detailed mechanisms including some therapeutic effects of ginger and its constituents for effective antioxidant properties were comprehensive reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 174 publications
0
50
0
1
Order By: Relevance
“…The association between phytochemicals and disease prevention has been a major focus of health researchers for almost half a century [ 58 , 59 , 60 ]. Several studies have demonstrated that naturally occurring bioactive compounds and phytochemicals have a broad spectrum of physiological effects, including alleviation of metabolic disorder, inflammation, and oxidative stress [ 61 , 62 , 63 ]. These studies suggest that the medicinal effects of various food commodities could provide new ways to develop dietary strategies to prevent many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The association between phytochemicals and disease prevention has been a major focus of health researchers for almost half a century [ 58 , 59 , 60 ]. Several studies have demonstrated that naturally occurring bioactive compounds and phytochemicals have a broad spectrum of physiological effects, including alleviation of metabolic disorder, inflammation, and oxidative stress [ 61 , 62 , 63 ]. These studies suggest that the medicinal effects of various food commodities could provide new ways to develop dietary strategies to prevent many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, (−)-epigallocatechin gallate represents up to 60–65% of the total catechins in tea [ 8 ]. Ginger ( Zingiber officinale ) root and Aloe vera , both rich in polyphenols (about 10–40 mg/100 g for ginger [ 9 ] and about 300 mg/100 g for aloe’s lyophilized leaf epidermis [ 10 ]), are examples of herbs that provide health benefits thanks to their high antioxidant activities [ 11 , 12 ]. Extra virgin olive oil (EVOO) displays many healthy properties, principally ascribed to minimal constituents in the unsaponifiable fraction, such as phenolic compounds, phytosterols, tocopherols, and pigments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, as a food additive approved by the European Food Safety Authority, is a yellow pigment isolated from Curcuma longa [7] , [8] , [9] , [10] . At present, several studies have reported that curcumin, activated by ultrasonic sound and blue LED light, showed desirable bactericidal activity against a range of bacteria, such as Staphylococcus aureus [11] , [12] , Pseudomonas aeruginosa [13] , and Escherichia coli [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%